I recently came across the problem:

$$\sum_{k=0}^{\infty} \frac{k!}{\prod_{j=0}^{k} \left(2j+3\right)}$$ and decided to try finding its solution. I started off by writing a program that gave me the answer $0.4292036732051...$ which I found probably meant the solution was $2-\frac{\pi}{2}$, but I wanted to see if I could prove it. I started by manipulating the denominator into a double factorial resulting in: $$\sum_{k=0}^{\infty} \frac{k!}{\left(2k+3\right)!!}$$ Then, I thought things would be easier to work with if I only had regular factorials. This gave me: $$\sum_{k=0}^{\infty} \frac{4\cdot2^k k! \left(k+2\right)!}{\left(2k+4\right)!}$$ I unfortunately had little clue to go from here considering I haven't dealt with factorials often, much less in infinite series such as this one. I am curious how it is possible to go forth from here and also how to solve infinite series that are similarly structured. Any help would be appreciated.

  • $\begingroup$ If we could find $\sum\limits_{k \ge 0} x^k/\binom{2k+4}{k+2},$ a bit of integration would seal the deal. $\endgroup$ – Display name Jan 24 at 8:03
  • $\begingroup$ By reindexing, we only need to know $\sum\limits_{k \ge 0} x^k/\binom{2k}{k}.$ $\endgroup$ – Display name Jan 24 at 8:04

We obtain \begin{align*} \sum_{k=0}^\infty\frac{k!}{(2k+3)!!}&=\sum_{k=0}^\infty\frac{k!(2k+2)!!}{(2k+3)!}\\ &=\sum_{k=0}^\infty\frac{k!2^{k+1}(k+1)!}{(2k+3)!}\\ &=\sum_{k=0}^\infty\binom{2k}{k}^{-1}\frac{2^k}{(2k+1)(2k+3)}\\ &=\sum_{k=0}^\infty\binom{2k}{k}^{-1}\frac{2^{k-1}}{2k+1}-\sum_{k=0}^\infty\binom{2k}{k}^{-1}\frac{2^{k-1}}{2k+3}\tag{1} \end{align*}

We use a representation of reciprocal binomial coefficients via the Beta function:

\begin{align*} \binom{n}{k}^{-1}=(n+1)\int_0^1z^k(1-z)^{n-k}\,dz\tag{2} \end{align*}

and the left-hand series of (1) can be calculated as

\begin{align*} \color{blue}{\sum_{k=0}^\infty\binom{2k}{k}^{-1}\frac{2^{k-1}}{2k+1}} &=\sum_{k=0}^\infty 2^{k-1}\int_0^1z^k(1-z)^k\,dz\tag{3}\\ &=\frac{1}{2}\int_{0}^{1}\sum_{k=0}^\infty \left(2z(1-z)\right)^k\,dz\\ &=\frac{1}{2}\int_{0}^1\frac{dz}{1-2z(1-z)}\tag{4}\\ &=\frac{1}{2}\int_{0}^{1}\frac{dz}{z^2+(1-z)^2}\\ &=\frac{1}{2}\int_{0}^{\infty}\frac{du}{1+u^2}\tag{5}\\ &\,\,\color{blue}{=\frac{\pi}{4}}\tag{6} \end{align*}


  • In (3) we use the identity (2).

  • In (4) we apply the geometric series expansion.

  • In (5) we use the substitution $u=\frac{1-z}{z}, du=-\frac{1}{z^2}dz$.

We also want to apply (2) to the right-hand series of (1). To do this conveniently we need some preparatory work: \begin{align*} \sum_{k=0}^\infty&\binom{2k}{k}^{-1}\frac{2^{k-1}}{2k+3}\\ &=\sum_{k=0}^\infty\frac{k!k!}{(2k)!}\cdot\frac{2^{k-1}}{2k+3}\\ &=\sum_{k=0}^\infty\frac{k!(k+1)!(2k+1)}{(2k+1)!(k+1)}\cdot\frac{2^{k-1}}{2k+3}\\ &=\sum_{k=0}^\infty\frac{(k+1)!(k+1)!}{(2k+2)!}\cdot\frac{2^{k+1}}{2k+3}-\sum_{k=0}^\infty\frac{k!(k+1)!}{(2k+1)!(k+1)}\cdot\frac{2^{k-1}}{2k+3}\\ &=\sum_{k=0}^\infty\binom{2k+2}{k+1}^{-1}\frac{2^{k+1}}{2k+3}-\sum_{k=0}^\infty\binom{2k}{k}^{-1}\frac{2^{k-1}}{(2k+1)(2k+3)}\\ &=\sum_{k=0}^\infty\binom{2k+2}{k+1}^{-1}\frac{2^{k+1}}{2k+3} -\sum_{k=0}^\infty\binom{2k}{k}^{-1}\frac{2^{k-2}}{2k+1} +\sum_{k=0}^\infty\binom{2k}{k}^{-1}\frac{2^{k-2}}{2k+3}\tag{7}\\ \end{align*} In the last line (7) we use a partial fraction decomposition as we did in (1).

We are now well prepared to do the calculation. We obtain together with (6):

\begin{align*} \color{blue}{\sum_{k=0}^\infty \binom{2k}{k}^{-1}\frac{2^{k-2}}{2k+3}} &=\sum_{k=0}^\infty\binom{2k+2}{k+1}^{-1}\frac{2^{k+1}}{2k+3}-\frac{\pi}{8}\\ &=\sum_{k=0}^\infty2^{k+1}\int_{0}^1z^{k+1}(1-z)^{k+1}\,dz-\frac{\pi}{8}\\ &=\sum_{k=1}^\infty2^k\int_{0}^1z^k(1-z)^k\,dz-\frac{\pi}{8}\\ &=\frac{\pi}{2}-2^0\int_{0}^1\,dz-\frac{\pi}{8}\\ &\,\,\color{blue}{=\frac{3}{8}\pi-1}\tag{8} \end{align*}

We finally conclude from (1) together with (6) and (8) \begin{align*} \color{blue}{\sum_{k=0}^\infty\frac{k!}{(2k+3)!!}} &=\sum_{k=0}^\infty\binom{2k}{k}^{-1}\frac{2^{k-1}}{2k+1}-\sum_{k=0}^\infty\binom{2k}{k}^{-1}\frac{2^{k-1}}{2k+3}\\ &=\frac{\pi}{4}-2\left(\frac{3}{8}\pi-1\right)\\ &\,\,\color{blue}{=2-\frac{\pi}{2}} \end{align*}

and the claim follows.

| cite | improve this answer | |

Starting from $$4\sum_{k=0}^{\infty} \frac{2^k k! \left(k+2\right)!}{\left(2k+4\right)!} $$Consider $$4\sum_{k=0}^{\infty}\frac{k! (k+2)!}{ (2 k+4)!}(2t)^{2k}$$ and, now, the trick is to recognize (not so obvious) that this is $$\frac{1}{t^2}-\frac{\sqrt{1-t^2} }{t^3}\sin ^{-1}(t)$$ Make $t=\frac 1 {\sqrt 2}$ and get the result.

| cite | improve this answer | |
  • $\begingroup$ This is helpful, but I don't understand anything about the final equivalence. Does this have something to do with a Taylor series or is it something else? $\endgroup$ – Kirk Fox Jan 25 at 3:21
  • $\begingroup$ @KirkFox. This is exactly the point ! It is the infinite Taylor expansion. As I wrote, it took me time to find it. Cheers :-) $\endgroup$ – Claude Leibovici Jan 25 at 3:33

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.